La Ciudad En El Cine: Una Perspectiva Mundial - Edelman, David J. (European Scientific Journal, ESJ, 2018)
Commercial cinema is a worldwide form of entertainment enjoyed by most of the planet’s population and variety of cultures. Films are produced on six continents and marketed successfully internationally. However, cinema is more than a medium for telling stories of adventure, intrigue, comedy and romance. As most of the world’s population now lives in cities, many films take place in urban settings, where a large number of those cities’ physical and social problems are exposed. Commercial film, then, plays a useful role in determining how such issues can be confronted through the lenses of their many countries and cultures. That is, solutions to urban problems must be culturally sensitive. Moreover, as cities dominate life on planet Earth in the 21st century far beyond what their population alone would warrant, they are at the core of some of the most influential films of the last century. This paper, then, is significant in that it looks at some of these urban focused films and identifies the universal themes they consider.